(untitled) (Revista Innova Educación, 2020)
Intertextuality, as a cross-linking of one meaning with another, refers to the link with other texts and the contributions they make to offer various interpretative and creative possibilities. It is considered a central element of the complexity of conceptual and semantic relationships to give meaning to communication, it incorporates and validates the culture of the subject in the democratization process in order to understand and participate in it. This research was carried out graduates of regular basic education to measure the domain of intertextuality, two prose readings were used, both by the writer and poet César Abraham Vallejo Mendoza, (1) Los Caynas, and (2) Beyond life and death, for the collection of information observable and measurable behavioral indicators were chosen, observation and a checklist were used. It was found that 62.1% was at the low level, 29.3% at the high level and 8.6% at the medium level. It is recommended that in future investigations, representative samples be used to compare and explain the literary competence and reading experience that would be basic elements of intertextuality.